Advances and challenges in 2D MXenes: From structures to energy storage and conversions. (October 2021) - Meng, Weixue; Liu, Xingjiang; Song, Haoqiang; Xie, Yu; Shi, Xiaolei; Dargusch, Matthew; Chen, Zhi-Gang; Tang, Zhiyong; Lu, Siyu
Highlights: Synthetic strategies for MXene used in energy storage and conversions. The complex based on MXene is discussed. MXene possess great advantages in energy storage. Challenges and opportunities in the future development of MXene based energy storage are considered. Graphical Abstract: ga1 Abstract: Since the discovery of Ti3 C2 in 2011, a class of 2D transition metal carbides and nitrides, called MXene, has received increasing attention. So far, about 30 different kinds of MXenes with clear structure and properties exist and more MXenes are theoretically predicted. As a consequence of their excellent metal conductivity, unique in-plane anisotropy, attractive optical, mechanical, and thermal properties, MXenes show great potential for many applications. This review highlights the fundamentals, synthesis, and properties of MXenes, and focuses on applications of MXenes in supercapacitors, batteries, sensors, electromagnetic shielding/absorption and catalysis. Finally, we point out the controversies, challenges, and future opportunities in MXenes.